2017
DOI: 10.1136/bmjgh-2017-000419
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of anxiety, depression and post-traumatic stress disorder in the Kashmir Valley

Abstract: BackgroundFollowing the partition of India in 1947, the Kashmir Valley has been subject to continual political insecurity and ongoing conflict, the region remains highly militarised. We conducted a representative cross-sectional population-based survey of adults to estimate the prevalence and predictors of anxiety, depression and post-traumatic stress disorder (PTSD) in the 10 districts of the Kashmir Valley.MethodsBetween October and December 2015, we interviewed 5519 out of 5600 invited participants, ≥18 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
75
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(82 citation statements)
references
References 43 publications
3
75
4
Order By: Relevance
“…Compared with other countries, the prevalence of mental distress in the present study was lower than reported in Canada [15], Malaysia [14], Cambodia [11] and Kashmir Valley in India [35]. The longitudinal community survey from Canada [11] which included 2433 men and women aged 15 to 65 years used the K-10 scale for mental distress while the Malaysian National Health and Morbidity Survey (2015) [14] used the General Health Questionnaires (GHQ-12) in a sample of individuals older than 15 years.…”
Section: Discussioncontrasting
confidence: 84%
See 3 more Smart Citations
“…Compared with other countries, the prevalence of mental distress in the present study was lower than reported in Canada [15], Malaysia [14], Cambodia [11] and Kashmir Valley in India [35]. The longitudinal community survey from Canada [11] which included 2433 men and women aged 15 to 65 years used the K-10 scale for mental distress while the Malaysian National Health and Morbidity Survey (2015) [14] used the General Health Questionnaires (GHQ-12) in a sample of individuals older than 15 years.…”
Section: Discussioncontrasting
confidence: 84%
“…The longitudinal community survey from Canada [11] which included 2433 men and women aged 15 to 65 years used the K-10 scale for mental distress while the Malaysian National Health and Morbidity Survey (2015) [14] used the General Health Questionnaires (GHQ-12) in a sample of individuals older than 15 years. The Cambodia study [15] and the Kashmir study [35] applied the Hopkins Symptoms Checklist-25 (HSCL-25) in adult populations. Variations in design, instruments and/or included ages across studies make comparison of prevalence of mental distress difficult.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[16,17] High prevalence of depression has also been reported in general Kashmiri population. [18] This may be due to the fact that people living in conflict are at a higher risk of developing psychological distress. [19] Double and triple co-existent illnesses were reported in 22.0% and 41.8% of participants, respectively.…”
Section: Discussionmentioning
confidence: 99%